Polymeric Blatter's Radical via CuAAC and ROMP. Issue 19 (12th September 2021) - Saal, Adrian; Friebe, Christian; Schubert, Ulrich S.
Abstract: A Blatter radical‐containing polymer backbone is synthesized via copper‐catalyzed azide‐alkyne cycloaddition (CuAAC) and consecutive ring‐opening metathesis polymerization. For this, an alkyne‐functionalized Blatter radical is synthesized and used for the described CuAAC, yielding a polymerizable derivative of the radical. The resulting polymer is electrochemically investigated in cyclic voltammetry experiments, paving the way for the possible utilization of triazinyl radicals in all‐organic polymer batteries. Furthermore, the simple modification of the alkyne bond makes further derivatization easily accessible. Abstract : A Blatter radical‐containing polymer is designed and synthesized via ring‐opening metathesis polymerization and further characterized electrochemically. The monomeric structure is prepared by coupling an alkyne‐functionalized Blatter radical with a norbornene structure in a copper‐catalyzed alkyne‐azide cycloaddition (CuAAC). This type of reaction is especially promising for an easy modification of the radicals under mild conditions.